BIOLOGICAL SIGNIFICANCE OF BIOLOGICALLY ACTIVE SUBSTANCES IN THE BODY, DISEASES ARISING FROM THE LACK OF BIOLOGICALLY ACTIVE SUBSTANCES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Biologically active substances are organic compounds necessary for the vital activity and normal metabolism of living organisms. Essential substances necessary for the human body in everyday life, i.e. vitamins A, B1, B2, B6, B12, D, K, play a very important role in the functioning of the human body. If one of these substances is lacking, it causes various diseases in the human body. The main source of vitamins is plants. Microorganisms They also play an important role in the production of vitamins. Its biological significance lies in its corrective effect on metabolism, intensifies the chemical reactions taking place in the body, affects the absorption of nutrients by the body, contributes to the normal growth of cells and the development of the entire body, the intake of enzymes into the body and their normal functioning. Vitamins are involved in energy metabolism in the body, the biosynthesis of amino acids and fatty acids, the process of photoreception (vitamin A), blood clotting (vitamin K) and the absorption of calcium (vitamin D). Thus, if the vitamin is absent or completely absent in the body, the metabolism is disrupted.